Needs Analysis for Developing a Motif-Orientation-Position-Size (MOP-Size) Framework in Karawo Textile Art Learning - Hasdiana Hasdiana; Abd. Kadim Masaong; Sitti Roskina Mas; Lukman AR Laliyo (Jurnal Pendidikan Terapan, 2026)
Purpose: This study aims to analyze students’ learning needs as the basis for developing a Motif-Orientation-Position-Size (MOP-Size) framework in Karawo textile art education, particularly in supporting students’ ability to translate motif knowledge into structured textile composition. Methods: A descriptive quantitative needs-analysis design was employed involving 45 Visual Arts Education students who had participated in Karawo textile learning. Data were collected using a 30-item Likert-scale questionnaire covering five dimensions: learning conditions, motif-placement understanding and difficulties, perceived need for the framework, application readiness, and expected benefits. Data were analyzed using descriptive statistics, including mean, standard deviation, frequency distribution, and category analysis. Findings: The results show that all dimensions were generally in the moderate category. However, the motif-placement dimension revealed the most critical gap, with 42.22% of students in the low and very low categories. Meanwhile, the need for the framework, readiness to apply it, and perceived benefits showed positive tendencies, indicating acceptance of structured learning support. Research Implications: The findings indicate that Karawo learning requires structured scaffolding to support students’ compositional decision-making. The MOP-Size framework is proposed as a preliminary instructional structure that can guide motif analysis, orientation testing, positional arrangement, and size scaling in textile design learning. Originality: This study introduces MOP-Size as a context-based instructional construct that operationalizes motif, orientation, position, and size as teachable variables in traditional textile education, particularly in Karawo learning.